Metaphor In The Lyrics Of Olivia Rodrigo’s Song On The Album “Sour” - Tuti Nur Hayati; Zulfa Nabila (Journal on Education, 2024)
Several songs from Olivia Rodrigo's album "SOUR" utilize metaphorical language to express emotions, feelings, and social critiques. This study aims to identify the types and functions of metaphors found in the album's lyrics. The applied methodology is qualitative descriptive, with data consisting of pop song lyrics. The analysis is supported by three main theories: those of Lakoff and Johnson (2003), Parera (2004), and Ullmann (2014). The study reveals that metaphorical words or phrases undergo a shift from lexical meaning to metaphorical meaning based on similarities in concepts, processes, states, attributes, forms, quantities, sensations, characters, or functions of the described objects or phenomena. The social realities depicted in the lyrics encompass individual behaviors and states, as well as expressions of both positive and negative behaviors. Findings indicate the presence of various types of metaphors, including anthropomorphic metaphors, shifts from abstract to concrete, synesthesia, strucktural, orientational, and personification.